2022
DOI: 10.33363/swjsa.v5i2.873
|View full text |Cite
|
Sign up to set email alerts
|

Kekerasan Simbolik terhadap Perempuan dalam Budaya Patriarki

Abstract: Berangkat dari beberapa penelitian sebelumnya, mahasiswa Sosiologi Agama pada umumnya telah mengerti persoalan-persoalan gender. Namun, pada kenyataannya, mereka masih mengalami kekerasan simbolik di ranah kebahasaan. Penelitian ini bertujuan untuk mengungkapkan kekerasan simbolik, khususnya dalam ranah bahasa, yang dialami oleh perempuan atau mahasiswi Sosiologi Agama di UIN Alauddin Makassar. Penelitian ini merupakan penelitian kualitatif. Penelitian ini menggunakan wawancara dan observasi sebagai metode pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…(Sugiarti, 2021) Previous research has discussed symbolic violence in various contexts, such as mass media, schools, and YouTube video content (Trisno, 2018). Several previous studies have also shown that symbolic violence can occur in basic student leadership training (Rinaldi, 2019), against women in a patriarchal culture (Alfian, 2022), in seniority in the educational environment (Pribadi, 2021), and in the use of mixed language among student.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…(Sugiarti, 2021) Previous research has discussed symbolic violence in various contexts, such as mass media, schools, and YouTube video content (Trisno, 2018). Several previous studies have also shown that symbolic violence can occur in basic student leadership training (Rinaldi, 2019), against women in a patriarchal culture (Alfian, 2022), in seniority in the educational environment (Pribadi, 2021), and in the use of mixed language among student.…”
Section: Introductionmentioning
confidence: 94%
“…The phenomenon of symbolic violence also occurs in social interaction, language, and norms that exist on campus. For example, in a journal there is a report that at Alauddin Makassar State Islamic University there are incidents of symbolic violence against women among students of Sociology of Religion related to patriarchal culture (Alam, 2022), then in other journals, it is written that symbolic violence is contained in the novel "Wounds of Smoked Women" is caused by the existence of power and authority relations that come from parties who have a more superior position in shaping campus culture. (Sugiarti, 2021) Previous research has discussed symbolic violence in various contexts, such as mass media, schools, and YouTube video content (Trisno, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Edukasi mengenai feminisme pun semakin digencarkan untuk menghindari kesalahpahaman mengenai maksud dan tujuan dari gerakan feminisme (Nathania Octaviani et al, n.d.). Meskipun telah banyak perjuangan dilakukan oleh manusia, terutama oleh kaum perempuan, patriarki masih berkembang dan tumbuh subur dengan segala macam bentuknya (Alam & Alfian, 2022). Pada era 5.0, di mana teknologi maupun keterhubungan global semakin meluas, pertanyaan tentang bagaimana budaya patriarki memengaruhi kehidupan mahasiswa UNESA, dan bagaimana mereka meresponsnya, menjadi semakin penting.…”
unclassified
“…Growing up in a patriarchal-agrarian culture, Bugis women are often said to have dominant roles in the kitchen, well, and bed. In the study of gender and feminism, patriarchal discourse is a violent discourse because it traps women in a low/inferior position by allowing men to determine standards for women on how to see, feel, think, and act in society (Alam & Alfian, 2022). Women are often placed in unfavorable positions (Akbar, 2022).…”
mentioning
confidence: 99%